Human Tracking Methods Comparison for Smart House Method Comparison in Human Tracking for Smart House Purpose - Gustave Lyman (ULTIMA InfoSys, 2014)
Smarthouse systems require some information of human locations in the system environment, different smart house system offers different human tracking method. The idea of this paper is to determine which method is better in which condition. This paper discusses amongst RFID, voice recognizer and temperaturesensor. As a result, each method have its own advantages and disadvantages. Index Terms - smart house, human tracking, voice recognition RFID, Sensor.